Plasmonic Photoelectrochemistry: In View of Hot Carriers. Issue 46 (12th May 2021) - Zhang, Yuchao; Guo, Wenxiao; Zhang, Yunlu; Wei, Wei David
Abstract: Utilizing plasmon‐generated hot carriers to drive chemical reactions has emerged as a popular topic in solar photocatalysis. However, a complete description of the underlying mechanism of hot‐carrier transfer in photochemical processes remains elusive, particularly for those involving hot holes. Photoelectrochemistry enables to localize hot holes on photoanodes and hot electrons on photocathodes and thus offers an approach to separately explore the hole‐transfer dynamics and electron‐transfer dynamics. This review summarizes a comprehensive understanding of both hot‐hole and hot‐electron transfers from photoelectrochemical studies on plasmonic electrodes. Additionally, working principles and applications of spectroelectrochemistry are discussed for plasmonic materials. It is concluded that photoelectrochemistry provides a powerful toolbox to gain mechanistic insights into plasmonic photocatalysis. Abstract : Photoelectrochemistry provides a powerful toolbox for mechanistic studies on hot‐carrier‐driven reactions in plasmonic photocatalysis. The working principles and applications of plasmonic photoelectrochemistry are summarized.